From the “integrated city” to “slums as an opportunity”: entrepreneurship, politics and “pacification” in Rio de Janeiro - Rocha, Lia de Mattos; Carvalho, Monique Batista (Pontifícia Universidade Católica de São Paulo, 2018)
The federal intervention in the public security area in the state of Rio de Janeiro, which started in February 2018, and the announcement of the partial extinction of the Pacifying Police Program, have raised the following question: what changes and what remains the same in the scenario of Rio’s slums after ten years of “pacification”? This article aims to answer this question, shedding light on one dimension of this process: the production of a new sociability in these territories, where entrepreneurship has presented itself as a fundamental element. Based on an ethnography carried out in slums with Pacifying Police Units, and on the monitoring of public and private projects executed at the time, we analyze the impact of this production on the associative life of these localities.